Photocatalytic Removal of Toxic Metals from Tannery Wastewater using Green Synthesized Zinc Oxide Nanoparticles - Tyosue Christopher Kpega; James Dama Habila; Idongesit Edem Okon; Patricia Adama Ekwumemgbo (ASEAN Journal for Science and Engineering in Materials, 2026)
Water is an important natural resource and is vital to all living organisms. However, increased industrialization and urbanization have led to water pollution. This research aimed at removing some toxic metals from tannery wastewater using already green synthesized zinc oxide nanoparticles (ZnO-NPs). The treatment method used was photocatalytic degradation. The concentrations of Cr, Cu, and Pb in the wastewater were found to be above the standard recommended by WHO and the National Environmental Standards Regulatory and Enforcement Agency (NESREA) while those of Ni, Mn, and Co were within the acceptable limit. The photocatalytic degradation using the ZnO-NPs was effective in the treatment of the metals: Cr, Co, Cu, Mn, Ni, and Pb as their concentration in the treated tannery wastewater were significantly lower than that in the untreated wastewater except for Mn. Based on the results, photocatalytic degradation using green synthesized ZnO-NPs has proven to be a viable method for the degradation of tannery wastewater.